Unearned Preferential Treatment: The Moderating Role of Power. (August 2015) - Zhang, Lu; Hanks, Lydia
Although upgrading an airline seat or a hotel room may seem like a simple way to delight a customer, it can sometimes have unintended consequences. Satisfaction with an unexpected upgrade could be lessened if others did not also receive it, particularly if those others were friends of the upgraded customer. Using a between-subjects design with a scenario and survey, we found that power moderated the effect of relationship status on individuals' satisfaction and behavioral intentions, such as repurchase and recommendation, when receiving unearned preferential treatment. Participants in the powerless condition exhibited lower satisfaction and behavioral intention when they were with friends who did not receive an upgrade, as compared with when they were with strangers. However, such a difference was not observed among participants in the powerful conditions. Managerial implications and ideas for future research are discussed.